2018
DOI: 10.3389/fpsyg.2018.01589
|View full text |Cite
|
Sign up to set email alerts
|

How a Good Sleep Predicts Life Satisfaction: The Role of Zero-Sum Beliefs About Happiness

Abstract: Sleep, although a vital aspect of human functioning, has received scant attention in happiness research. This research examines the effect of sleep quality on life satisfaction, and one possible mechanism that bridges the two. One cognitive factor that might tie the relationship between sleep and life satisfaction is a belief about the (in) finite nature of happiness (zero-sum belief about happiness; ZBH), a mindset that occurs more under conditions of scarcity. Given the interconnections among experiences pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 21 publications
3
43
0
1
Order By: Relevance
“…A substantial body of research demonstrates the impact of lifestyle on mental health and subjective well-being ( Walsh, 2011 ; Prendergast et al, 2016 ; Atzendorf et al, 2018 ; Lianov et al, 2019 ; Wang and Geng, 2019 ; Ingram et al, 2020 ). Specifically, a healthier diet ( Piqueras et al, 2011 ; Blanchflower et al, 2013 ; Rooney et al, 2013 ; White et al, 2013 ), higher quantity and quality of sleep ( Shin and Kim, 2018 ; Zhao et al, 2019 ) and more physical activity ( Khazaee-Pool et al, 2015 ; Murphy et al, 2018 ; Zhang and Chen, 2019 ) have been shown to lead to higher happiness. Thus, research has established that healthy lifestyle behaviors can make people happier.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…A substantial body of research demonstrates the impact of lifestyle on mental health and subjective well-being ( Walsh, 2011 ; Prendergast et al, 2016 ; Atzendorf et al, 2018 ; Lianov et al, 2019 ; Wang and Geng, 2019 ; Ingram et al, 2020 ). Specifically, a healthier diet ( Piqueras et al, 2011 ; Blanchflower et al, 2013 ; Rooney et al, 2013 ; White et al, 2013 ), higher quantity and quality of sleep ( Shin and Kim, 2018 ; Zhao et al, 2019 ) and more physical activity ( Khazaee-Pool et al, 2015 ; Murphy et al, 2018 ; Zhang and Chen, 2019 ) have been shown to lead to higher happiness. Thus, research has established that healthy lifestyle behaviors can make people happier.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Using equation (2), the regression and the variable coefficients are significant at the 5% level, but the economic freedom index is only significant at the 8% level. Building on Gropper, Lawson and Thorne [11] and given the correlation between GDP and economic freedom, an interaction term is tested using equation (3). Under this specification, all the model variables are significant at the 1% level.…”
Section: Second Model Specificationmentioning
confidence: 99%
“…The annual costs of inadequate sleep as a percentage of GDP are estimated to reach 3.3%, 2.6%, 1.8%, 1.6%, and 1.5%, by the year 2030, in Japan, United States, United Kingdom, Germany and Canada respectively [2]; such cost estimates relate to mortality and work productivity effects of inadequate sleep. Sleep has received little attention in happiness research, whether from the medical or the economic point of view [3,4]. While the link between sleep and life satisfaction could be bi-directional, there is evidence that good sleep might affect how positively a person evaluates their life [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is construed as a stable personality characteristic. The positive effects of optimism have been demonstrated across diverse, stressful situations (53,62). The positive effects of optimism could be mediated through positive coping strategies, for example, optimists use more problem-focused strategies-information seeking and positive reframing (62).…”
Section: Discussionmentioning
confidence: 99%